(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Awiqli 700 Units FlexTouch is an antidiabetic medicine used to treat diabetes mellitus in adults. It works like the body’s natural insulin to help keep blood sugar levels under control by moving sugar from the blood into the body’s cells. It also reduces the amount of sugar made by the liver. Use Awiqli 700 Units FlexTouch exactly as prescribed by your doctor. It is injected under the skin once a week, preferably on the same day each week. Monitor your blood sugar regularly as advised, follow your recommended meal plan and exercise routine. Do not stop or change your insulin dose without consulting your doctor. The most common side effect of Awiqli 700 Units FlexTouch is low blood sugar (hypoglycemia), which may cause sweating, shakiness, dizziness, hunger, headache, or confusion. If this happens, check your blood sugar and treat it immediately. Oteh common side effects include hypersensitivity, Injection site reactions, itching, rash, and weight gain. Inform your doctor if any side effects persist or worsen. Do not use Awiqli 700 Units FlexTouch if you are allergic to insulin icodec or any of its ingredients. Avoid missing meals, strenuous physical activity, or taking more insulin than prescribed, as that may increase the risk of low blood sugar. If you are taking pioglitazone with insulin, inform your doctor immediately if you develop symptoms such as shortness of breath or swelling, as this combination may increase the risk of heart failure in some people.